The Psychology of Social Status - Cheng, Joey T.; Tracy, Jessica L.; Anderson, Cameron; SpringerLink (Online service) (New York Springer Science+Business Media, 2014)
Given the far-reaching effects of status on human societies, understanding the psychology of social status is crucial. Across all societies, differences in social rank or status not only determine who leads and who follows, but also the ways in which individuals resolve conflicts, allocate goods and resources, and coordinate to achieve shared group goals. The Psychology of Social Status outlines the foundational insights, key advances, and developments that have been made in the field thus far. The goal of this volume is to provide an in-depth exploration of the psychology of human status, by reviewing each of the major lines of theoretical and empirical work that have been conducted in this vein. Organized thematically, the volume covers the following areas: - An overview of several prominent overarching theoretical perspectives that have shaped much of the current research on social status. - Examination of the personality, demographic, situational, emotional, and cultural underpinnings of status attainment, addressing questions about why and how people attain status. - Identification of the intra- and inter-personal benefits and costs of possessing and lacking status. - Emerging research on the biological and bodily manifestation of status attainment - A broad review of available research methods for measuring and experimentally manipulating social status A key component of this volume is its interdisciplinary focus. Research on social status cuts across a variety of academic fields, including psychology, sociology, anthropology, organizational science others; thus the chapter authors are drawn from a similarly wide-range of disciplines. Encompassing the current state of knowledge in a thriving and proliferating field, The Psychology of Social Status is a fascinating and comprehensive resource for researchers, students, policy-makers, and others interested in learning about the complex nature of social status, hierarchy, dominance, and power.
Preface and acknowledgments -- Joey T. Cheng, Jessica L. Tracy, and Cameron Anderson -- Part I. Theoretical Perspectives: The Nature of Social Status and Hierarchy -- Chapter 1.Toward a unified science of hierarchy: Dominance and prestige are two fundamental pathways to human social rank Joey T. Cheng and Jessica L. Tracy -- Chapter 2. Prestige and the ongoing process of culture revision Jerome H. Barkow Chapter 3. Do status hierarchies benefit groups? A bounded functionalist account of status Cameron Anderson and Robb Willer -- Chapter 4. What$1 (Bs in a name? Status, power, and other forms of social hierarchy Steven L. Blader and Ya-Ru Chen -- Part II. Who Leads? Psychological Underpinnings of Status Attainment -- Chapter 5. Personality and status attainment: A Micropolitics perspective -- Cameron Anderson and Jon Cowan -- Chapter 6.The status-size hypothesis: How cues of physical size and social status influence each other Nancy M. Blaker and Mark van Vugt -- Chapter 7. Prosocial behavior and social status -- Sara Kafashan, Adam Sparks, Vladas Griskevicius, and Pat Barclay -- Chapter 8.The pursuit of status: A self-presentational perspective on the quest for social value Mark R. Leary, Katrina P. Jongman-Sereno, and Kate J. Diebels -- Chapter 9. The roots and fruits of social status in small-scale human societies Christopher von Rueden -- Chapter 10.The emotional underpinnings of social status Conor M. Steckler and Jessica L. Tracy -- Part III. Intrapsychic and Interpersonal Consequences of Status -- Chapter 11. Decision-making at the top: Benefits and barriers Nathanael J. Fast and Priyanka D. Joshi -- Chapter 12. Social categories create and reflect inequality: Psychological and sociological insights Michael S. North and Susan T. Fiske -- Part IV. How is Status Manifested in the Body? Chapter 13. Hormones and hierarchies Erik L. Knight and Pranjal H. Mehta Chapter 14. Neural basis of social status hierarchy Narun Pornpattananangkul, Caroline F. Zink, Joan Y. Chiao -- Chapter 15. Nonverbal communication and the vertical dimension of social relations Judith A. Hall, Ioana-Maria Latu, Dana R. Carney, Marianne Schmid Mast -- Part V. Methodology -- Chapter 16. The assessment of social status: A review of measures and experimental manipulations Joey T. Cheng, Aaron C. Weidman, and Jessica L. Tracy. .s
Keywords: Personality; Social psychology; Social structure; Social inequality; Anthropology; Personality and Social Psychology; Social Structure, Social Inequality; Anthropology